Proceedings of the 20th ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming 2015
DOI: 10.1145/2688500.2688542
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of asynchronous graph processing on GPU with hybrid coloring model

Abstract: Modern GPUs have been widely used to accelerate the graph processing for complicated computational problems regarding graph theory. Many parallel graph algorithms adopt the asynchronous computing model to accelerate the iterative convergence. Unfortunately, the consistent asynchronous computing requires locking or the atomic operations, leading to significant penalties/overheads when implemented on GPUs. To this end, coloring algorithm is adopted to separate the vertices with potential updating conflicts, guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
13
0
2
Order By: Relevance
“…In other words, the result of the offloaded task is not required by other tasks for their execution. Asynchronous execution split up the problem into multiple tasks and process them independently [26], [27]. A real-life example of asynchronous execution is discussion forums where every user can post their views independent of any other user.…”
Section: Terminologiesmentioning
confidence: 99%
“…In other words, the result of the offloaded task is not required by other tasks for their execution. Asynchronous execution split up the problem into multiple tasks and process them independently [26], [27]. A real-life example of asynchronous execution is discussion forums where every user can post their views independent of any other user.…”
Section: Terminologiesmentioning
confidence: 99%
“…GraphR [9] 也采用这种分割方式, 利用 ReRAM 的存储特性来设计高性能低功耗的图计算加速器. [24] , Medusa [25] , MapGraph [26] , Frog [27] 等都是前面提到的 CSR 的布局方式, 这种存 储模式可以压缩图数据占据的内存空间大小. 但是使用 CSR 会在运算过程中对顶点属性的访问产生 很大的随机性, 造成了大量的随机访问.…”
Section: 图计算常见编程模型unclassified
“…[Gemini [16] , CPU, 2016], [Frog [27] , GPU, 2015], [Page [46] , CPU, 2015], [GraphReduce [31] , GPU, 2015], etc.…”
Section: 新兴存储器技术利用新兴存储器技术将计算逻辑集成在存储器内是一个很好的降低能耗的方式 例如 前所述的 Hmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work indicated that asynchronous approaches have the potential to minimize the effects of load imbalance across different cores in multicore machines [18]. GraphLab [19], PowerGraph [20], and other distributed frameworks [21,22] have investigated the use of asynchronous execution models, which could implement the traversal operations in general. However, these approaches are more suitable for the distributed, batch-oriented graph computation that runs on the entire graph, instead of interactive traversal and query of subgraphs, which are common in our HPC-rich metadata management system.…”
Section: Introductionmentioning
confidence: 99%